2022
DOI: 10.1111/1471-0307.12901
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of vitamin K forms in cheese and their potential role in cardiovascular disease

Abstract: Vitamin K collectively describes fat‐soluble vitamins containing 2‐methyl‐1,4‐naphthoquinone, including two naturally‐occurring forms: phylloquinone (K1) and a range of menaquinones, MK4‐M13 (K2). Leafy vegetables are the main dietary source of K1, whereas K2 is mainly bacterially synthesised and found in fermented foods, including dairy foods, and some animal sources. Studies suggest that vitamin K may be important for cardiovascular health, due to its role in inhibiting vascular calcification, but food sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…For instance, this effect has been attributed to the metabolites produced by bacteria contained in the cheese . Vitamin K is a group of fat-soluble vitamins (K1, K2, K3), which have a potential role in cardiovascular disease, due to inhibiting vascular calcification …”
Section: Multifunctionality Of Bioactive Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, this effect has been attributed to the metabolites produced by bacteria contained in the cheese . Vitamin K is a group of fat-soluble vitamins (K1, K2, K3), which have a potential role in cardiovascular disease, due to inhibiting vascular calcification …”
Section: Multifunctionality Of Bioactive Compoundsmentioning
confidence: 99%
“…57 Vitamin K is a group of fat-soluble vitamins (K1, K2, K3), which have a potential role in cardiovascular disease, due to inhibiting vascular calcification. 58 A study of a randomized, double-blind, placebo-controlled trial, reported by Asoudeh et al, 59 examined patients with mild to moderate severity of rheumatoid arthritis who received 30 g/day of probiotic cheese for 12 weeks. In this sense, the presence of probiotics might be beneficial as adjuvant therapy for preventing rheumatoid arthritis.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…2021; Zhou et al . 2022). However, several studies have revealed that obesity, diabetes, atherosclerosis, hyperlipidaemia, gallstones and gout are generally attributed to the massive intake of fat‐rich foods, especially full‐fat cheese (Khaodhiar et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that all these nutrients together may reduce the potential risk of cardiovascular diseases (Feeney et al, 2021). According to Zhou et al (2022), fermented cheeses contain vitamin K2, which is also associated with benefits in preventing cardiovascular health.…”
Section: Introductionmentioning
confidence: 99%